Physiological effects of the use of elicitors in tomato crop in soil infested by Nacobbus aberrans - Martínez, Susana Beatriz (2020)
Measurement of plant physiological response to stress or practices for its alleviation is useful for non-destructive evaluation and early diagnosis. The aim of this work was to study physiological effect of the use of phytohormones on tomato crop in soil infested by Nacobbus aberrans. The essay was carried out under a greenhouse located in EE Julio Hirschhorn (La Plata, Buenos Aires). Tomato Elpida was treated by drench, 24 hours pre-transplanting with 1 ml of: salicilic acid 0.50 x 10-4 M and 1.00 x 10-4 M, ethylen 0.35 x 10-3 M and 0.70 x 10-3 M, jasmonic acid 1.00 x 10-4 M and 1.00 x 10-5 M, using plants without treatment as control. It was recorded gas exchange: CO2 net assimilation rate, stomatal conductance, transpiration and instant water use efficiency, leaf temperature and greenness index. Statistical design was a randomized complete block with 4 replications. Variance analysis and Tukey test were applied. Gas exchange was not modified by treatments. Leaf temperature was significant lesser with salicylic acid 1.00 x 10-4 M, which increased the greenness index; variable that was lower in control plants. Increasing resistance in tomato against N. aberrans by salicylic acid and the measurement of physiological variables to check the response of the plant are promising possibilities.